1986
DOI: 10.1073/pnas.83.22.8784
|View full text |Cite
|
Sign up to set email alerts
|

1,3-Di(2-[5-3H]tolyl)guanidine: a selective ligand that labels sigma-type receptors for psychotomimetic opiates and antipsychotic drugs.

Abstract: Brain a-type receptors are thought to mediate hallucinogenic effects of certain benzomorphan opiates in humans. The biochemical characterization of or receptors has been difficult because of the lack of potent and selective ligands. We report here the synthesis and characterization of a tritiated, symmetrically substituted guanidine derivative, 1,3-di(2- [

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
145
0

Year Published

1987
1987
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 286 publications
(149 citation statements)
references
References 25 publications
(17 reference statements)
4
145
0
Order By: Relevance
“…The high binding affinity of [12,13]. However, these ligands bind with 5-6-fold lower affinity than [3H]-lb.…”
Section: Discussionmentioning
confidence: 99%
“…The high binding affinity of [12,13]. However, these ligands bind with 5-6-fold lower affinity than [3H]-lb.…”
Section: Discussionmentioning
confidence: 99%
“…Prior to then, many investigators confirmed the ability of select antidepressant drugs, including selective serotonin reuptake inhibitors (SSRIs), monoamine oxidase inhibitors, and tricyclic antidepressants (TCAs), to interact with σ receptors (Schmidt et al, 1989;Itzhak and Kassim, 1990;Weber et al, 1986).…”
Section: Introductionmentioning
confidence: 99%
“…The rats were administered with one dose diary during 27 days, either of the sigma agonist 1,3-di-o-tolyl-guanidine (DTG; Tocris Biosciences) 10 mg/kg (i.p. ), [50] or phosphate buffer saline (vehicle).…”
Section: Drug Administrationmentioning
confidence: 99%